"Can I Sing You My Song?" Songwriting in Elementary Music with Community Artist Mentors. (March 2022) - Gallo, Donna; Kuchenbrod, Emily
In this article, we situate songwriting in elementary spaces as a vehicle for personal and musical expression and informed by popular music practices. We offer insights for how educators can anchor students' work by encouraging them to create songs for a specific purpose like shedding light on social issues relevant to their lives. This article also addresses how community songwriters might support the creative musicianship of elementary students and the ways in which they can offer unique mentorship to students when they share musical interests and lived experiences. We offer pedagogical ideas and considerations for engaging elementary students in songwriting, and we connect these ideas to a recent elementary school songwriting project in partnership with community artists.